Macroeconomic Shocks and the Endogenous Response of the Stock Market and Real Interest Rates in a Neoclassical General-Equilibrium Model - Kong, Weng Ho (Institutional Knowledge at Singapore Management University, 1995)
This paper develops a neoclassical general equilibrium model to study the endogenous response of the stock market and the term structure of real interest rates in the face of a number of macroeconomic shocks believed to be important in the 1980s. An exogenous decline in savings, a debt-financed fiscal expansion, an increase in investment subsidy and an anticipation of higher productivity growth are found to have contrasting effects on the value of the stock market and the behaviour of the term structure of real interest rates in the model closed economy.